2020
DOI: 10.2139/ssrn.3720459
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy Effects in Times of Negative Interest Rates: What do Bank Stock Prices Tell Us?

Abstract: Do negative interest rates matter for bank performance? This paper investigates whether monetary policy surprises impact bank stock prices differently in times of positive and negative interest rates. The analysis controls for broad stock market movements and finds that an unanticipated downward shift in the yield curve and a flattening of the shorter-end of the yield curve resulting from monetary policy announcements reduce bank stock prices in a low and especially negative interest rate environment. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Most of these studies find that reductions in central banks' policy rate, if carried out under LIRE, prompt a decrease in banks' profitability, both realized and expected. This latter result is in contrast with previous empirical evidence according to which conventional expansionary monetary policy, when implemented in a more traditional interest rate setting, would raise banks' stock market values by feeding economic activity and, hence, improving banks' prospected profitability (see Bats et al, 2020;Ampudia and Van den Heuvel, 2022). Borio et al (2017) go further and claim that the positive relation between central banks' policy rate and banks' profitability is highly non-linear.…”
Section: Literature Reviewcontrasting
confidence: 93%
See 2 more Smart Citations
“…Most of these studies find that reductions in central banks' policy rate, if carried out under LIRE, prompt a decrease in banks' profitability, both realized and expected. This latter result is in contrast with previous empirical evidence according to which conventional expansionary monetary policy, when implemented in a more traditional interest rate setting, would raise banks' stock market values by feeding economic activity and, hence, improving banks' prospected profitability (see Bats et al, 2020;Ampudia and Van den Heuvel, 2022). Borio et al (2017) go further and claim that the positive relation between central banks' policy rate and banks' profitability is highly non-linear.…”
Section: Literature Reviewcontrasting
confidence: 93%
“…Borio et al (2017), Altavilla et al (2017), andClaessens et al (2018) look 'backward' at realized profits only. Altavilla et al (2017), as well as Bats et al (2020) and Ampudia and Van den Heuvel (2022), extend the analysis to expected future banks' profits as captured by banks' stock market values. Most of these studies find that reductions in central banks' policy rate, if carried out under LIRE, prompt a decrease in banks' profitability, both realized and expected.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…By contrast, they do not find such a reversal for long term surprises. Bats et al (2020) measure equity returns for a smaller group of banks, controlling for broad stock market movements, and argue that flattening the yield curve has a smaller negative effect on bank profitability than a yield curve shift. Taken together, these studies add evidence that deposit margin effects are dominant in leading to negatively affected bank profitability.…”
Section: Notesmentioning
confidence: 99%
“…As mentioned above, besides simple correlations, these papers have used high-frequency identification, exposure-measure regressions, or cross-country regressions. The papers using high-frequency identification, like Ampudia and van den Heuvel (2019), Bats et al (2020), or Wang (2019), have typically found detrimental effects on bank stock prices from negative rate implementation.…”
Section: Introductionmentioning
confidence: 99%